Passing into the present : contemporary American fiction of racial and gender passing - Moynihan, Sinéad (Contemporary American and Canadian writers., 2010)
This book is a full-length study of contemporary American fiction of 'passing'. It takes as its point of departure the return of racial and gender passing in the 1990s in order to make claims about wider trends in contemporary American fiction.